2019
DOI: 10.1007/s00431-019-03486-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of opioid withdrawal in neonates with morphine, phenobarbital, or chlorpromazine: a randomized double-blind trial

Abstract: Three suitable compounds (morphine, chlorpromazine, and phenobarbital) to treat neonatal abstinence syndrome were compared in a prospective multicenter, double-blind trial. Neonates exposed to opioids in utero were randomly allocated to one of three treatment groups. When a predefined threshold of a modified Finnegan score was reached, treatment started and increased stepwise until symptoms were controlled. If symptoms could not be controlled with the predefined maximal dose of a single drug, a second drug was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Morphine decreases the ticagrelor plasma concentration [30], the combination of gabapentin with morphine produces better anaesthesia even when administered at low dose [32], and morphine is associated with a delayed onset of action of oral antiplatelet agents [33]. The treatment of infants and children with morphine has been extensively studied [34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphine decreases the ticagrelor plasma concentration [30], the combination of gabapentin with morphine produces better anaesthesia even when administered at low dose [32], and morphine is associated with a delayed onset of action of oral antiplatelet agents [33]. The treatment of infants and children with morphine has been extensively studied [34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Morphine is able to control withdrawal symptoms in infants exposed to opioids in utero [34]. Newborns, with neonatal abstinence syndrome, were treated with morphine which significantly produces higher scores in cognitive and gross motor domains compared to infants treated with methadone [35].…”
Section: Treatment Of Infants and Children With Morphinementioning
confidence: 99%
“…Given emerging concerns on the meaningfulness of the Finnegan score as a primary outcome, we focused analyses on pharmacotherapy (AMT, CMD, and LOT) and hospitalization duration (length of stay). We did not recalculate the sample size post hoc; calculations reported in other studies indicated our study sample size was adequate to detect differences (Supplement 1).…”
Section: Methodsmentioning
confidence: 96%
“…Currently, morphine and methadone are recommended for opioid therapy of mNOWS for severe symptoms of withdrawal by the American Academy of Pediatrics (Hudak et al, 2012;Lacaze-Masmonteil & O'Flaherty, 2018), with morphine being the most widely used (Tolia et al, 2015). When compared in a multicenter, double-blind, prospective parallel group study in neonatal intensive care units, morphine, phenobarbital, and chlorpromazine show some efficacy, but morphine was more likely to treat symptoms of withdrawal in mNOWS without requiring a second agent (Zimmermann et al, 2020). Morphine and methadone show similar short-term and long-term (18 months of age) neurobehavioral outcomes when used for treatment of mNOWS (Czynski et al, 2020), but methadone is associated with shorter hospitalization (Tolia et al, 2018), while buprenorphine shows superiority over other opioids in decreasing both treatment duration and length of stay (Disher et al, 2019;Kraft et al, 2017;Lee et al, 2019).…”
Section: Opioid Therapy With Morphine Methadone or Buprenorphinementioning
confidence: 99%